Pengaruh Fluktuasi Harga Cabai Rawit Merah Terhadap Inflasi di Kabupaten Banyumas - Wahyuni, Tri Septi; Satriani, Ratna; Mandamdari, Alpha Nadeira (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Changes in food commodity prices are the biggest contributor to the inflation rate due to fluctuating food prices, one of which is red cayenne pepper which often experiences price spikes on holidays due to the supply of red cayenne pepper in the market that cannot meet consumer demand. Banyumas Regency experiences a high spike in the price of red cayenne pepper and one of the contributors to the inflation in Banyumas Regency. This study aims to 1) To determine the price movement of red cayenne pepper in Banyumas Regency from 2017 to 2023. 2) Identify the effect of red cayenne pepper price fluctuations on inflation in Banyumas Regency. This research is a quantitative descriptive research using VAR (Vector Autoregression) and VECM. The results showed that the price of red cayenne pepper in Banyumas Regency experienced a significant price spike at the beginning of the year and Eid al-Fitr, namely in March to June for the period 2017 to 2023 and experienced a price decline in September to November due to Central Java experiencing a bumper harvest. Fluctuations in the price of red cayenne pepper in Banyumas Regency in the short term significantly affect the value of inflation but in the long term do not significantly affect inflation. In the first period the price of red cayenne pepper contributed to the inflation by 13.57% and in the long term contributed 23,61%.